A review of base isolation systems with adaptive characteristics. (April 2022) - Sheikh, Hediyeh; Van Engelen, Niel C.; Ruparathna, Rajeev
Abstract: Base isolation systems are widely used as an effective and practical solution to protect the structure and non-structural elements from seismic hazards. However, the excessive displacement under severe events may cause damage to the bearing as well as the structure. The growth in seismic isolation technology has led to the development of innovative base isolation systems which exhibit adaptive behavior. The behavior is denoted adaptive when the properties of the device change substantially depending on the loading level. Thus, the response can be tailored to the hazard level based on the softening and subsequent stiffening response and/or changing damping ratio as displacement increases. Recently, the concept of adaptive behavior has gained significant attention within the research community. This review presents the development and current knowledge base of adaptive devices in the absence of active control means. Some types of adaptive devices have the remarkable ability to dissipate the input energy at severe events, which leads to seismic mitigation of the floor acceleration and interstory drift of the superstructure at all hazard levels. Others can effectively reduce the responses at low to moderate earthquake ground motions while limiting the displacement at extreme events.